„Drzwi zamknięte” czy „otwarte bramy”, czyli tłumacz między profanum a sacrum - Kubaszczyk, Joanna (Poznańskie Studia Teologiczne, 2018)
The paper reflects on the specificity of the translation of texts belonging to the religious and theolog- ical literature. Religious and theological texts have been translated for millennia, many of them — originating in the sphere of Judeo-Christianity — lie at the core of Western culture. Their trans- lation, especially the translation of the Bible, was accompanied by theoretical reflection (see, for example, Jerome of Stridonium, Martin Luther or Eugene Nida), which permanently influenced the way of thinking about translation in general. The present study answers the question of how the translation of religious and theological texts differs from the translation of other texts and what the translator must or should take into account, translating religious and theological texts. The paper discusses, among others, the role of the word in Christianity, spiritual preparation, openness to the Holy Spirit, tradition and inculturation.